Renal function and histology after acute hemorrhage in rats under dexmedetomidine action - Marangoni,Marco Aurelio (2007)
PURPOSE: About 50 % of indications for dialysis in acute renal failure are related to problems originated during the perioperative period. Intraoperative hemodynamic changes lead to renal vasoconstriction and hypoperfusion. Previous studies have not defined the dexmedetomidine renal role in hemorrhage situations. This study evaluated the effect of dexmedetomidine on renal function and histology after acute hemorrhage in rats. METHODS: Covered study with 20 Wistars rats, anesthetized with sodium pentobarbital, 50 mg. kg-1, intraperitoneal, randomized into 2 groups submitted to 30% volemia bleeding: DG - iv dexmedetomidine, 3 µg. kg-1 (10 min) and continuous infusion - 3 µg. kg-1. h-1; CG - pentobarbital. For renal clearance estimative, sodium p-aminohippurate and iothalamate were administered. Studied attributes: heart rate, mean arterial pressure, rectal temperature, hematocrit, iothalamate and p-aminohippurate clearance, filtration fraction, renal blood flow, renal vascular resistance, and histological evaluations of the kidneys. RESULTS: DG showed smaller values of heart rate, mean arterial pressure, and renal vascular resistance, but iothalamate clearance and filtration fraction values were higher. There was similarity in p-aminohippurate clearance and renal blood flow. Both groups had histological changes ischemia-like, but dexmedetomidine determined higher tubular dilatation scores. CONCLUSION: In rats, after acute hemorrhage, dexmedetomidine determined better renal function, but higher tubular dilation scores.